Analisis Metode Praktikum Berbasis Literasi Sains pada Pembelajaran IPA Kelas VII di SMP Swasta Bhayangkari 3 - Sari, Ginanjar; Sari, Novi Fitriandika; Dimenta, Rivo Hasper (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
Studies on contemporary scientific education have shown that classroom teaching has an impact on students' use of literacy-deficient practical exercises. Consequently, the existing approach of teaching science is significantly deficient and must be substituted. The objective of this descriptive qualitative research is to assess the effectiveness of the Science Literacy-Based Practicum Method in Science Instruction for seventh grade students at SMP Swasta Bhayangkari 3. The sample for this study consisted of thirty seventh graders from SMP Swasta Bhayangkari. Both teachers and students were provided with a questionnaire to complete, and data was gathered via interviews based on their responses. The results indicate that 19.94% of students demonstrate a strong understanding of scientifically explaining phenomena. Additionally, 8.60% of students are able to evaluate and design scientific investigations, while 9.28% of students understand how to interpret data and evidence. According to the findings of this research, integrating a practicum focused on literacy into the learning process is an effective method for promoting student performance and attaining learning goals.